2012
DOI: 10.1101/lm.026393.112
|View full text |Cite
|
Sign up to set email alerts
|

Localization of molecular correlates of memory consolidation to buccal ganglia mechanoafferent neurons after learning that food is inedible in Aplysia

Abstract: Training paradigms affecting Aplysia withdrawal reflexes cause changes in gene expression leading to long-term memory formation in primary mechanoafferents that initiate withdrawal. Similar mechanoafferents are also found in the buccal ganglia that control feeding behavior, raising the possibility that these mechanoafferents are a locus of memory formation after a training paradigm affecting feeding. Buccal ganglia mechanoafferent neurons expressed increases in mRNA expression for the transcription factor ApC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 76 publications
0
30
0
Order By: Relevance
“…As in numerous previous studies examining learning that food is inedible in Aplysia (Botzer et al, 1998; Katzoff et al, 2002, 2006; Levitan et al, 2012), 24 hr before being trained animals were transferred to 10 L experimental aquaria that were maintained at room temperature (23°C). They were kept two to an aquarium, with the two animals separated by a partition allowing the flow of water.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As in numerous previous studies examining learning that food is inedible in Aplysia (Botzer et al, 1998; Katzoff et al, 2002, 2006; Levitan et al, 2012), 24 hr before being trained animals were transferred to 10 L experimental aquaria that were maintained at room temperature (23°C). They were kept two to an aquarium, with the two animals separated by a partition allowing the flow of water.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…In some experiments, training proceeded until the animals stopped responding to food, which was defined as a lack of entry of food into the mouth for 3 min. In experiments in which the initial training was continued until the animals stopped responding (full training), data were included only from animals in which food was in the mouth eliciting failed attempts to swallow for at least 100 s, since previous experience (Levitan et al, 2012) showed that such animals almost always show long-term memory. Animals in which food was not in the mouth for 100 s during a full training were discarded.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning that food is inedible in Aplysia is a complex associative learning task in which animals attempt to eat a tough food, but fail to swallow it (Susswein et al 1986;Botzer et al 1998;Katzoff et al 2002;Levitan et al 2008Levitan et al , 2010Levitan et al , 2012Michel et al 2010Michel et al , 2011Michel et al , 2012Levy et al 2016;Lyons et al 2017). The task is nonetheless relatively easily studied, and some of the physiological and molecular correlates of the learning have been identified (Levitan et al 2008(Levitan et al , 2012Michel et al 2010Michel et al , 2011Levy et al 2016). In this task, animals progressively decrease their responses to a particular food, and eventually stop responding to it, while maintaining their response to other foods (Schwarz et al 1988).…”
mentioning
confidence: 99%
“…Performance was measured by the accumulated time the food was kept in the mouth cavity (total mouth time) and the total time the animal engaged in biting and spitting the food (total response time). Animals with ,200 sec of accumulated mouth time or a total response time ,600 sec during Training were excluded from analysis (n ¼ 4), as previous studies indicated that these animals show unreliable learning outcome, and to homogenize the groups with regard to training performance (Levitan et al 2012). Results were analyzed using analysis of variance including a group factor representing the Sleep and Wake groups and a repeated-measures factor representing the different test occasions (Training, Retrieval 1, and Retrieval 2).…”
mentioning
confidence: 99%